Design of Sales Information Systems and Receivable Control at UD Eka - I Made Dhira Wiradana; Arifin Puji Widodo; Teguh Sutanto (Jurnal Sistem Informasi Universitas Dinamika, 2018)
UD Eka is a manufacturing company that sells goods as well as raw materials for footwear manufacture such as soles and heels. The products will be sold to several distributors, while for the sale of basic raw materials the manufacture of footwear is marketed to the craftsmen outside the company. In conducting sales activities to customers, UD Eka has problems in providing credit limit to customers who have bad credit record. So that will result in stalled credit payments by customers in the future. In addition, the company also experienced the problem of lack of good oversight of the company's receivables. Based on the problems currently problem, then made a system that can solve these problems. From these transactions can generate accounts receivable age, maturity receivable report, maturity receivable report, customer contribution report, product contribution report, customer sales trend report, and product sales trend report. From the test results, applications that have been made to generate reports related to sales and control of receivables that are expected to assist companies in making decisions related to the number of bad debts.